Designing and validation of an instrument for the assessment of dietary habits, physical activity, sun exposure and sleeping patterns among community-based Saudi adults - Farahat, Mohamed F.; Alam, Iftikhar; Aldisi, Dara; Mahmoud , Mohamed H.; Abulmeaty, Mahmoud M. A. (Progress in Nutrition, 2023)
Background and aim: The prevalence of diet-related diseases has risen rapidly. Changes in certain lifestyle factors (dietary habits, physical activity, sun exposure, and sleeping patterns) are the key to understanding these diseases. Most of the previous research studies investigated these factors separately and hence any interrelationships that may exist among these factors is not much clear due to the lack of a comprehensive instrument that determines these factors at a time in a collective manner. Therefore, the aim of this study was to design and validate an instrument that assesses these lifestyle factors in a comprehensive way. Methods: The design and validation of the instrument were carried out in four distinct phases: a) literature review and existing instruments; b) design of the instrument c) sample selection of experts (N = 14); and d) quantitative (Likert-type scale from 1 to 5) and qualitative assessment of the degree of relevance of each of the 36 items included in the instrument. Aiken’s V coefficient was used to determine content validity. Likewise, internal consistency was calculated using Cronbach’s α-coefficient. Results: The final questionnaire had 4 parts to cover data on dietary habits, physical activity, sun exposure, and sleeping patterns. The questionnaire was also greatly improved by the qualitative comments of the experts, which were incorporated. For most of the items, the results showed demanding levels of validity (V ≥ 0.76), internal consistency (α= 0.915), and inter-rater, and intra-rater reliability. Conclusion: Therefore, it is a valid and reliable instrument that makes possible a complete assessment of dietary intake, physical activity, sun exposure, and sleeping patterns in the adult Saudi population.